Bureaucratic and Political Collaboration Towards a Good Governance System - Nurfaika Ishak; Rahmad Ramadhan Hasibuan; Tri Suhendra Arbani (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This research aims to know how is the synergy of bureaucracy and politics in realizing good governance. More specifically, what are the factors that influence the relationship between bureaucracy and politics in realizing good governance system. This study used a qualitative approach which is give description about the issues. The data collection technique used is literature study by examining and analyzing relevant literature such as books, journal articles, laws and regulations focusing bureaucracy, politics, and good governance systems. The results of the research showed that the synergy between bureaucracy and politics is absolutely necessary to realize good governance system. In addition, factors that affects relationships between them are aspect of authority/ power, human resources, and recruitment system. Bureaucracy and politics must be placed in the same stage to prevent superiority between bureaucracy and politics. A balanced relationship can be transformed into juridical restrictions. The empowerment of professionals in filling bureaucracy and politics must be prioritized in order to reduce corruption and nepotism that occurs in irrational recruitment systems. Keywords: Bureaucracy; Good Governance; Politics.